The effects of dorsal bundle injections of 6-hydroxydopamine on avoidance responding in rats. - Fibiger, H C (1978)
1 The effect of injection of 6-hydroxydopamine (6-OHDA) into the fibres of the dorsal noradrenergic bundle on acquisition, retention and extinction of active avoidance in rats were examined. 2 6-OHDA injections severely depleted noradrenaline in all forebrain areas assayed, with the interesting exception of the septum. No significant effect on dopamine concentrations in various forebrain regions was found. 3 Acquisition and retention of active avoidance was not altered by the lesion. Marked resistance to extinction was seen when the unconditioned stimulus (shock) was removed. 4 A comparison with work by other authors in which both forebrain noradrenaline and dopamine were depleted suggest that the alteration in extinction seen in both studies is a noradrenergic effect, whereas the deficits in acquisition and retention found previously are dopaminergic in origin.